PENDEKATAN FILOSOFIS DALAM PENGELOLAAN LEMBAGA PENDIDIKAN ISLAM BERLANDASKAN NILAI DAN ETIKA DI MADRASAH ALIYAH AL-AMIRIYYAH DARUSSALAM - Arrosyad, Fahmi Hasbi; Rosidi, Sofyan; Rofiq, Ainur (Hijri, 2025)
The main objective of this research is to analyze and formulate a philosophical approach to the management of Islamic educational institutions at Madrasah Aliyah Aliyah Al-Amiriyyah Darussalam, based on values and ethics, in order to produce a holistic, ethical, and contextual management model. This research uses a qualitative approach with a case study method to explore the application of a philosophical approach in the management of Madrasah Aliyah Aliyah Al-Amiriyyah Darussalam, based on values and ethics. The research subjects included the madrasah principal, teachers, administrative staff, students, and parents. Data were collected through semi-structured interviews, participant observation, and documentation, then analyzed thematically with triangulation for validity. Philosophical reflection served as an analytical framework, linking the findings to the ontological, epistemological, and axionomic principles of Islamic education, to formulate a holistic, ethical, and contextual management model. The management of Madrasah Aliyah Al-Amiriyyah Darussalam applies a philosophical approach based on Islamic values and ethics, so that management focuses not only on administrative matters but also on the holistic development of students' character, morals, and spirituality. A foundation of values and ethics forms the basis for decision-making, while philosophical reflection helps balance operational demands with broader educational goals. A values-based collaborative approach engages teachers, staff, students, and parents, strengthening social legitimacy, community participation, transparency, and accountability. This practice integrates modern management principles of Ethical Management, Transformational Leadership, Participative Leadership, and Community-Based Educational Management with Islamic educational philosophy, enabling madrasahs to become models of holistic, ethical, contextual, and sustainable educational management.??